Tratado de los contratos - Jean Olivi, Pierre de (Historia del Derecho, 2017)
This book contains the Treatise of contracts of the Provençal Franciscan Pierre de Jean Olivi (1248-1298), in an annotated translation into Spanish by Pedro Ramis-Serra and Rafael Ramis-Barceló, author of a comprehensive preliminary study that revises the historical, legal and institutional background of Olivi, as well as an analysis of the reception of the profile and works by Olivi during the Modern Era. The Treatise of Contracts was the first great Theological-Legal-Economical Treatise on the matter, and it opened a path which, eventually and in the Modern era, was especially fruitful for theologians, jurists and canonists.-----Este libro contiene el Tratado de los contratos del franciscano provenzal Pierre de Jean Olivi (1248-1298), en traducción anotada al español de Pedro Ramis Serra y Rafael Ramis Barceló, autor éste de un amplio estudio preliminar que explica el marco histórico, jurídico e institucional de Olivi, así como un análisis de la recepción de la figura y obra de Olivi en la Modernidad. El Tratado de los contratos fue primer gran tratado teológico-jurídico-económico sobre la materia, y abrió un camino que, a la postre y en la época moderna, fue especialmente fecundo tanto para teólogos, como para legistas y canonistas.